Pengaruh Indeks Maqashid Syariah dan Ukuran Perusahaan terhadap Profitabilitas - Leviana Belianti; Ruhadi Ruhadi; Setiawan Setiawan (Indonesian Journal of Economics and Management, 2022)
Maqashid sharia is the direction of Islamic bank activities in obtaining profit. This topic is interesting to be researched because profitability in Islamic perspective is a material and immaterial benefit obtained in the world and the hereafter. This study aims to explore the effect of Islamic maqashid index and company size on profitability of Sharia Common Banks in Indonesia in the 2014-2018 period. The research method used explanatory causality with multiple regression analysis using WarpPLS 6.0 program. The data used are secondary data from 12 samples of Sharia Common Banks in Indonesia. The results of this study indicate that the maqashid sharia index also the company size has a positive significant effect on profitability. The greater maqashid index and size of a sharia commercial bank will be able to increase the profitability of sharia banks which reflects companies that adhere to sharia maqashid compliance and optimal in gaining profits.